Գոյականի հոլովական զուգաձեւությունների կառուցատիպերը Ե. դարի մատենագրական երկերում - Լալիկ Խաչատրյան; Լւսինե Ենգոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматриваются надежные параллелизмы в историографических трудах Егише, П.Бюзанда, Х.Парпеци, Лгафангсль и М.Хоренаци. In the article the declension doublets are being examined in the historiographic works of Eghishe, Ph. Buzand, Gh. Parpetsy, Agaphangel and M. Khorenatsy.
Keywords: Language and Literature